2016
DOI: 10.1016/j.avb.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Making ‘what works’ work: A meta-analytic study of the effect of treatment integrity on outcomes of evidence-based interventions for juveniles with antisocial behavior

Abstract: This study meta-analytically examined the effect of treatment integrity on client outcomes of evidence-based interventions for juveniles with antisocial behavior. A total of 17 studies, from which 91 effect sizes could be retrieved, were included in the present 3-level meta-analysis. All included studies, to a certain level, adequately implemented procedures to establish, assess, evaluate and report the level of treatment integrity. A moderator analysis revealed that a medium-to-large effect of evidence-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…A small but statistically significant relationship was identified between therapist adherence and youth outcome, suggesting that implementing the appropriate components of therapy plays a small role in child and adolescent therapeutic practice. This finding is in line with a previous qualitative review of child and adolescent mental health intervention and prevention [17], and with a meta-analysis of intervention for juvenile antisocial behaviour [19], although it appears inconsistent with the meta-analysis by Webb et al [16]. This suggests, if taken at face value, that therapist adherence may be marginally more influential in child and family settings compared with adult individual therapy settings.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A small but statistically significant relationship was identified between therapist adherence and youth outcome, suggesting that implementing the appropriate components of therapy plays a small role in child and adolescent therapeutic practice. This finding is in line with a previous qualitative review of child and adolescent mental health intervention and prevention [17], and with a meta-analysis of intervention for juvenile antisocial behaviour [19], although it appears inconsistent with the meta-analysis by Webb et al [16]. This suggests, if taken at face value, that therapist adherence may be marginally more influential in child and family settings compared with adult individual therapy settings.…”
Section: Discussionsupporting
confidence: 69%
“…A recent systematic review of child and adolescent cognitive behavioural therapy concluded that the understanding of the relationships between adherence or competence and outcome remains inconclusive [18]. In contrast, a recent meta-analysis has indicated a relationship between integrity and outcome in intervention for juvenile antisocial behaviour [19]. These findings suggest, in line with inferences drawn based on individual studies, that implementation may be associated with outcome in some child and adolescent intervention approaches but not others.…”
mentioning
confidence: 99%
“…The intercoder reliability study on the OAT-A and EAT-A is a first step to enable systematic AT evaluation with a child diagnosed ASD. As indicated before there is until now not a will contribute to improvement of treatment results as was documented in several studies (Goense et al 2016;Town et al, 2012).…”
Section: Recommendationsmentioning
confidence: 91%
“…These consensus-based elements are related to the art making processes of children diagnosed with ASD and to the behaviour of the art therapists. Both 'areas of defined typical elements' are assumed to be crucial for achieving positive outcomesGoense et al, 2016; Van Lith, Stallings, & Harris, 2017; Van Yperen, Van der Steege, Addink, & Boendermaker, 2010). Consensus-based elements typical for AT with children diagnosed ASD can contribute to a 'promising' level of practice-based evidence (Van Yperen, Veerman, & Bijl, 2017).…”
mentioning
confidence: 99%
“…Program fidelity-the extent to which a program or service is delivered in the way it was prescribed to be-is a core indicator of implementation success (Breitenstein et al, 2010;Kramer & Burns, 2008). Systematic and meta-analytic reviews consistently report high levels of fidelity to be linked with better client outcomes; conversely, low levels of fidelity were associated with an absence of positive treatment effects (Durlak & DuPre, 2008;Goense, Assink, Stams, Boendermaker, & Hoeve, 2016). Hence, without evidence of program fidelity, it is not possible to attribute improvements in client outcomes to program effects.…”
Section: Implementation: Concepts and Definitionsmentioning
confidence: 99%